Literasi Qur’an Sebagai Upaya Peningkatan Hubbul Qur’an Melalui Kegiatan Muqoddaman di Desa Karangtejo - Ngathoillah Linnaja; Neli Maghfiroh; Aulia Fitri Musyafa; Firda Dina Sabrina; Fatkhu Salam; Azzam Haikal Makhfudh; Nurlaila Hidayatul Maghfiroh; Asri Sugesti; Umar Said Assegaf; Aulia Elfina Nur Rizki; Athi’ Karimah; Muhfid Al Munawar; Indra Wahyu Pratama; Muhammad Azildan Adilfi (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2025)
One of the main components that forms the religious character of Muslims is reading the Qur’an. However, there are still problems in Karangtejo Village in increasing understanding and love of the Al-Qur’an(hubbul Qur’an), especially among teenagers. This research aims to analyze the role of Muqoddaman activities in increasing Qur’an literacy and building love for the Qur’an in the Karangtejo Village community. This research, which took place in Karangtejo Village, was carried out using a qualitative approach using observation, interviews and documentation. Research shows that carrying out muqoddaman activities improves the ability to read the Qur’an properly and correctly as well as understanding what is in it, and can also build habits in implementing Islamic teachings in everyday life. Apart from that, muqoddaman activities can improve relationships between people and raise awareness of the importance of the Al-Qur’anas a guide to life. The benefit of this research is that it provides insight into the effectiveness of muqoddaman as a method of increasing Qur’an and hubbul Qur’an literacy. Thus, it is hoped that this research can become a reference for the government, educational institutions and society in developing strategies to increase Qur’an literacy in order to form a generation of Muslims who are religious, have noble character and adhere firmly to Islamic teachings.